N6-methyladenosine RNA methylation: From regulatory mechanisms to potential clinical applications - Li, Peipei; Wang, Yuntao; Sun, Yiwen; Jiang, Sanjie; Li, Jingjing (Frontiers in Cell and Developmental Biology, 2022)
Epitranscriptomics has emerged as another level of epigenetic regulation similar to DNA and histone modifications. N6-methyladenosine (m6A) is one of the most prevalent and abundant posttranscriptional modifications, widely distributed in many biological species. The level of m6A RNA methylation is dynamically and reversibly regulated by distinct effectors including methyltransferases, demethylases, histone modification and metabolites. In addition, m6A RNA methylation is involved in multiple RNA metabolism pathways, such as splicing, localization, translation efficiency, stability and degradation, ultimately affecting various pathological processes, especially the oncogenic and tumor-suppressing activities. Recent studies also reveal that m6A modification exerts the function in immune cells and tumor immunity. In this review, we mainly focus on the regulatory mechanisms of m6A RNA methylation, the techniques for detecting m6A methylation, the role of m6A modification in cancer and other diseases, and the potential clinical applications.